The Ottawa Self-Injury Inventory: Evaluation of an assessment measure of nonsuicidal self-injury in an inpatient sample of adolescents - Nixon, Mary K; Levesque, Christine; Preyde, Michèle; Vanderkooy, John; Cloutier, Paula F (Université d'Ottawa | University of Ottawa, 2015)
Abstract Background The Ottawa Self-Injury Inventory (OSI) is a self-report measure that offers a comprehensive assessment of nonsuicidal self-injury (NSSI), including measurement of its functions and addictive features. In a preliminary investigation of self injuring college students who completed the OSI, exploratory analysis revealed four function factors (Internal Emotion Regulation, Social Influence, External Emotion Regulation and Sensation Seeking) and a single Addictive Features factor. Rates of NSSI are particularly high in inpatient psychiatry youth. The OSI can assistin both standardizing assessment regarding functions and potential addictive features and aid case formulation leading to informed treatment planning. This report will describe a confirmatory factor analysis (CFA) of the OSI on youth hospitalized in a psychiatric unit in southwestern Ontario. Methods Demographic and self-report data were collected from all youth consecutively admitted to an adolescent in-patient unit who provided consent or assent. Results The mean age of the sample was 15.71 years (SD = 1.5) and 76 (81 %) were female. The CFA proved the same four function factors relevant, as in the previous study on college students (χ 2(183) = 231.98, p = .008; χ 2/df = 1.27; CFI = .91; RMSEA = .05). The model yielded significant correlations between factors (rs = .44-.90, p < .001). Higher NSSI frequency was related to higher scores on each function factor (rs = .24-.29, p < .05), except the External Emotion Regulation factor (r = .11, p > .05). The factor structure of the Addictive Features function was also confirmed (χ 2(14) = 21.96, p > .05; χ 2/df = 1.57; CFI = .96; RMSEA = .08). All the items had significant path estimates (.52 to .80). Cronbach’s alpha for the Addictive Features scale was .84 with a mean score of 16.22 (SD = 6.90). Higher Addictive Features scores were related to more frequent NSSI (r = .48, p < .001). Conclusions Results show further support for the OSI as a valid and reliable assessment tool in adolescents, in this case in a clinical setting, where results can inform case conceptualization and treatment planning.